Long-term athlete development - Balyi, I.; Cardinal, C.; Higgs, C.; Norris, S.; Way, R.
4 Glossary of Terms 7 Overview 8 An Outline of LTAD 13 Introduction 14 Sport System Alignment and Integration 17 Shortcomings and Consequences 19 The 10 Key Factors Influencing LTAD 19 The 10-Year Rule 20 The FUNdamentals 22 Specialization 23 Developmental Age 25 Trainability 28 Physical, Mental, Cognitive, and Emotional Development 28 Periodization 31 Calendar Planning for Competition 32 System Alignment and Integration 34 Continuous Improvement 36 Stages of LTAD 37 Active Start 38 FUNdamentals 40 Learning to Train 41 Training to Train 42 Training to Compete 43 Training to Win 44 Active for Life 46 Impact of LTAD 46 On Parents 46 On Coaching 47 On the Sport System 47 On Sport Science 48 On the Education System Canadian Sport Working Together 46 On Clubs and Community Sport and Recreation 49 Implementation 50 Summary 52 Selected Bibliography 54 Appendix 1 Physical, Mental, Cognitive, and Emotional Development 62 Appendix 2 65 Acknowledgements Table of Contents Sport Specific Charts